2018
DOI: 10.1071/sr18099
|View full text |Cite
|
Sign up to set email alerts
|

Conditions affecting oxide quantification in unknown tropical soils via handheld X-ray fluorescence spectrometer

Abstract: Soil chemical characterisation has been accurately performed worldwide using portable X-ray fluorescence (pXRF), contributing to fast, low-cost and environmentally-friendly soil analyses. However, many factors can influence the pXRF performance. Thus, this work was carried out to assess the oxides (SiO2, Al2O3, Fe2O3, TiO2 and P2O5) in tropical soils via pXRF, evaluating the effects of soil packing prior to analysis and the soil matrix. The packing of soil samples was performed using X-ray thin-film and common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In a preliminary study, only Fe 2 O 3 and TiO 2 yielded adequate fit values for linear regressions (Silva et al, 2018). Santana et al (2018) found adequate results for predicting SAD Fe 2 O 3 and TIO 2 for Brazilian soils. In this study, this trend was confirmed in addition to an adequate adjustment for P 2 O 5 contents, which has not been previously reported.…”
Section: Simple Linear Regression Modeling and Predictionsmentioning
confidence: 83%
See 1 more Smart Citation
“…In a preliminary study, only Fe 2 O 3 and TiO 2 yielded adequate fit values for linear regressions (Silva et al, 2018). Santana et al (2018) found adequate results for predicting SAD Fe 2 O 3 and TIO 2 for Brazilian soils. In this study, this trend was confirmed in addition to an adequate adjustment for P 2 O 5 contents, which has not been previously reported.…”
Section: Simple Linear Regression Modeling and Predictionsmentioning
confidence: 83%
“…Again, as SAD quantifies mainly the elemental content of the clay fraction (Resende et al, 1987), portions of Si and Al detected by pXRF were not quantified by SAD, hindering an adequate fit of linear regressions between these values. Another factor that may have influenced the adjustment of these prediction models is the low recovery values obtained for Si and Al, probably due to factors that influence the pXRF analysis, such as particle size, moisture, sample weight, sample preparation, data collection, and instrument alignment (Weindorf et al, 2014;Silva et al, 2018;Santana et al, 2018;Ribeiro et al, 2018;Peinado et al, 2010), although the samples of this study were analyzed in similar conditions regarding these influencing factors. In fact, this may be a constraint to the pXRF analysis if such factors are not taken into account.…”
Section: Simple Linear Regression Modeling and Predictionsmentioning
confidence: 99%
“…The pXRF analysis is fast, non-destructive, environmentally friendly, allowing the determination of several elements simultaneously (e.g., from Mg to U) in-situ or ex-situ within the order of seconds. The Soil Science has been greatly benefited from pXRF analysis (Ribeiro et al, 2017;Ribeiro et al, 2018;Santana et al, 2018;Silva et al, 2018;Mancini et al, 2019, Weindorf et al, 2014Stockmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid determination of SiO2, Al2O3, and Fe2O3 allow for the development of easy, in-field weathering indices supporting the soil classification and soil-related studies (Stockmann et al, 2016). Santana et al (2018) found that pXRF satisfactorily assessed the Fe2O3 content in several Brazilian soil samples compared to sulfuric acid digestion.…”
Section: Descriptive Statistics Of Pxrf Datamentioning
confidence: 75%